2019
DOI: 10.2478/adms-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Erosion Resistance Influence of Material Properties

Abstract: The cavitation erosion is the phenomena that causes degradation of fluid flow machinery components due to repetitive implosion of cavitation bubbles adjacent to the solid surface. Cavitation erosion is a complex phenomenon, which includes not only hydrodynamic factors of liquid, but also properties of erodible material e.g. microstructure, hardness or Young modulus. In order to reduce the negative impact of erosion on machine components, there are many methods to increase cavitation erosion resistance. The pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 72 publications
0
11
0
2
Order By: Relevance
“…Moreover, it was observed that the CuAlNi alloy in as-cast condition is softer (344 HV10) than after quenching (480 HV10), which suggested that resistance to cavitation erosion is better after quenching than that in the as-casted state. This is in contrast to the behaviour of other materials, which show that higher hardness of the materials gives better resistance to cavitation erosion [20]. This area definitely requires further investigation.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Moreover, it was observed that the CuAlNi alloy in as-cast condition is softer (344 HV10) than after quenching (480 HV10), which suggested that resistance to cavitation erosion is better after quenching than that in the as-casted state. This is in contrast to the behaviour of other materials, which show that higher hardness of the materials gives better resistance to cavitation erosion [20]. This area definitely requires further investigation.…”
Section: Resultsmentioning
confidence: 76%
“…Figure 4 shows the micrographs of microstructure in both as-cast and quenched states, before and after 420 min of exposure to cavitation testing obtained by an optical Cavitation erosion is a phenomenon that includes not only properties of liquid, but also the properties of material, for example, hardness, microstructure, grain size of material, and so on. It is known [20] that the material with a homogeneous and fine-grained structure has the highest cavitation erosion resistance, good mechanical properties, and high corrosion resistance. In the literature, there is no information about cavitation resistance testing of CuAlNi shape memory alloys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…microstructure, mechanical properties, material surface morphology, etc. [8,9]. Moreover, according to the literature [10][11][12], the abrasive wear and particularly sliding wear are dominant processes of materials degradation.…”
Section: Introductionmentioning
confidence: 99%